2002
DOI: 10.1080/09712119.2002.9706358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Giant Panda(Ailuropoda melanoleuca)Between Big and Small Populations

Abstract: Fang, S.G., Wan,Q.H. and Fujihara, N. 2002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This was in good agreement with a previous study that used 9 microsatellite markers to show that the XXL population had the highest level of allelic richness [9]. The XXL population, which is currently 1 of the smallest and most fragmented populations, experienced a drastic population reduction (60-fold) approximately 250 years ago [15], which suggests that the population should have undergone genetic drift and a rapid loss of genetic diversity [12]. However, contrary to this expectation, XXL was found to have the highest level of genetic variability.…”
Section: Discussionsupporting
confidence: 93%
“…This was in good agreement with a previous study that used 9 microsatellite markers to show that the XXL population had the highest level of allelic richness [9]. The XXL population, which is currently 1 of the smallest and most fragmented populations, experienced a drastic population reduction (60-fold) approximately 250 years ago [15], which suggests that the population should have undergone genetic drift and a rapid loss of genetic diversity [12]. However, contrary to this expectation, XXL was found to have the highest level of genetic variability.…”
Section: Discussionsupporting
confidence: 93%
“…Small populations result in the loss of bands specific to individuals, while relatively small populations result in a decline in the average number of total bands [24,25]. We therefore expect a loss of individual-specific bands in each population.…”
Section: Patterns Of Genetic Differentiation In the Giant Pandamentioning
confidence: 99%
“…However, Lu et al (2001) concluded that panda populations still retained considerable genetic diversity when compared against other carnivorous species, which was insured by Wan et al (2003). Fang et al (2002Fang et al ( , 2003 found the genetic variation in giant panda populations has a relationship with the number of individuals and that larger populations possessed relatively higher genetic variation than smaller populations. Wan et al (2003Wan et al ( , 2005 indicated that the Qinling population had diverged into a new subspecies (A. m. qinlingensis) when compared to the original subspecies (A. m. melanoleuca) in Sichuan.…”
Section: Introductionmentioning
confidence: 96%